Reanimaciòn cerebro-cardiopulmonar (RCCP) en un hospital de tercer nivel de atenciòn (2011)
Esta investigación analizó la intervención del equipo de salud en siete pacientes que persentaron para cardiorrespiratorio. Los procedimientos de recolección de la información incluyeron entrevistas con el equipo de salud y observaciones no participativas que permitieron reconocer la valoración y  diagnósitco del paciente en paro; la organización del equipo de salud; las técnicas y procedimientos durante la intervención de reanimación, y las sugerencias para mejorar la calidad de atención. Fueron importantes las manifestaciones de capacitación de todo el equipo de salud y la organización dinámica del  recurso humano y disponibilidad de material para actuar de manera coordinada y efectiva en toda situación; teniendo en cuenta que el tiempo y la eficiente atención son determinantes en la vida presente y futura de una persona. ABSTRACTThis investigation was carried out for the method of study of cases, where seven situations of unemployment cardio respiratory were analyzed, that which was made by means of observations non participative that were registered in work squares, where the following aspects erete contemplated: valuation and diagnosis of the unemployment cardio respiratory, organization of the team of health, technical and procedures used durin the intervention; they were also carried out interviews structured to the team of health that intervened, where the opinion of them was known as for facilities, limitations and suggestions about the human resource and material. Keeping in mind that the time is a decisive factor for the patient's life, this investigation showed the importance to organize a dynamics of opporune, efficient and effective performance, where each member of the team of health should have clarity about the functions that she will carry out during the intervention; equally the necessity is shown of having the whole material resource for the resuscitation in the service in that it is presented the unemployment cardio respiratory and its good operation.